Low Velocity Impact Responses of Functionally Graded Plates. (2017) - Singh, Hariveer; Hazarika, Bulon Ch.; Dey, Sudip
Abstract: The present study is dealt with the effect of low velocity impact responses of a functionally graded plates. The modified Hertzian contact law is employed in order to account for permanent indentation. The Power law is utilized for the graded characterization of functional material properties. The time dependent constitutive equations are solved by Newmark's time integration scheme. The results are obtained by using code which is validated. The transient low velocity impact response parameters such as contact force, plate displacement, impactor displacement and velocity of impactor are obtained to portray the effects of oblique impact angle and twist angle for aluminum-zirconia functionally graded plates.